Aplikasi Metode New Jersey untuk Menentukan Cadangan Premi Asuransi Jiwa Berjangka - Safitri Nurrohmah; Onoy Rohaeni (Jurnal Riset Matematika, 2022)
Abstract. Life insurance is one of the guarantees for the risk of death that can be followed by all circles of society. Insurance participants will be required to pay premiums that have been previously agreed with the insurance company and recorded in the insurance policy. The insurance company as the insurer will provide benefits of a sum of money to insurance participants in the event of a disaster or event. Seeing this phenomenon, the company must prepare reserves that have been previously prepared and calculated correctly so that the company does not suffer losses. The data in this study used the case of a 29 year old female and male insured who took a term life insurance product for 12 years and the payments were made every three months. The purpose of this study is to calculate premium reserves that must be prepared by insurance companies on term life insurance products using the New Jersey method. The New Jersey method is used to calculate premium reserves for which payments are more than twenty times. The fundamental thing to determine the value of the premium reserve using the New Jersey method is to know the age of the insurance participant and the period of coverage . Knowing the chance of life, the chance of someone dying which is presented in the interest rate and the amount of compensation that will be obtained by insurance participants. Based on the calculation results, the premium reserve that must be prepared by the insurance company for male insured is greater than the reserve value for a female insured. Abstrak. Peserta asuransi jiwa mempunyai kewajiban untuk membayar premi sessaui dengan kesepakatan. Perusahaan asuransi akan memberikan sejumlah uang berupa manfaat, yang sebelumnya sudah dikelola dari premi yang terlah dibayarkan oleh peserta asuransi. Melihat fenomena tersebut maka perusahaan harus menyiapkan cadangan yang sebelumnya sudah disiapkan dan dihitung dengan tepat agar perusahaan tidak mengalami kerugian. Data dalam penelitian ini menggunakan kasus seorang tertanggung perempuan dan laki-laki berusia 29 tahun mengambil produk asuransi jiwa berjangka selama 12 tahun dan pembayarannya dilakukan setiap tiga bulan sekali. Tujuan dari penelitian ini adalah untuk menghitung cadangan premi yang harus disiapkan oleh perusahaan asuransi pada produk asuransi jiwa berjangka dengan menggunakan metode New Jersey. Metode New Jersey digunakan untuk menghitung cadangan premi yang pembayarannya lebih dari dua puluh kali. Hal mendasar untuk menentukan nilai cadangan premi dengan menggunakan metode New Jersey yaitu mengetahui usia peserta asuransi dan jangka waktu pertanggungan . Mengetahui peluang hidup, peluang meninggal seseorang yang disajikan dalam tabel Mortalitas, tingkat suku bunga dan besernya santunan yang akan didapat oleh peserta asuransi. Berdasarkan hasil perhitungan, cadangan premi yang harus disiapkan oleh perusahaan asuransi untuk seorang tertanggung laki-laki lebih besar nilai cadangannya dibandingkan dengan seorang tertanggung perempuan.